Commercial opportunity for healthy snacks for children´s parties in metropolitan Lima - Abad, Gustavo A. (2024)
Childhood obesity is one of the nutritional problems with increasing numbers nationwide, related to the availability and proximity of foods high in fat and sugar such as those found at children's parties. There is a need to improve eating habits in boys and girls, as well as to have healthy options on the market aimed at children's parties. The objective of the research was to know the commercial opportunity for healthy snacks at children's parties, considering consumption characteristics, distribution channels and importance of the value proposition. The sample was 97 parents with children under 12 years, belonging to districts that house the highest percentage of families with socioeconomic levels A and B, to whom a 21-question survey was applied virtually through Google Forms. 100 % of parents indicated that they would be willing to buy healthy snacks for children's parties, 95 % choosing social networks and the website as the main distribution channel, 95.9 % preferred delivery service and 90.7 % valued the use of eco-friendly packaging. The average they would pay for healthy snacks is S/ 565.77 and the value for mode was S/ 500. The preferred payment methods were transfer and credit card. The results reveal an important commercial opportunity related to the interest of respondents in having healthy snack options at children's parties following current purchasing, delivery and environmental care trends.